2022
DOI: 10.1186/s12884-022-04839-0
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adverse childhood experiences and associations with prenatal substance use and poor infant outcomes in a multi-country cohort of mothers: a latent class analysis

Abstract: Background This paper enumerates and characterizes latent classes of adverse childhood experiences and investigates how they relate to prenatal substance use (i.e., smoking, alcohol, and other drugs) and poor infant outcomes (i.e., infant prematurity and low birthweight) across eight low- and middle-income countries (LMICs). Methods A total of 1189 mother-infant dyads from the Evidence for Better Lives Study cohort were recruited. Latent class anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…However, several studies showed that it was a particular ACEs class, but not the high/ multiple ACEs group, that was associated with the worst outcomes. For example, infants of mothers in the emotionally and physically abused group with intrafamilial violence exposure showed significantly low birth weight (Hemady et al, 2022); the class of household poverty and child discrimination showed the highest unmet care coordination needs (Anyigbo et al, 2021); children in the class of parental mental illness and poverty demonstrated the highest chronic condition and special healthcare needs (Lanier et al, 2018); adolescents experiencing neighborhood violence had the most severe chronic school absenteeism (Stempel et al, 2017); women in the sexual abuse/household dysfunction ACEs class had the weakest partner social support network during pregnancy (Napier et al, 2023); and adults experiencing sexual abuse were most vulnerable to developing diabetes (Salas et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, several studies showed that it was a particular ACEs class, but not the high/ multiple ACEs group, that was associated with the worst outcomes. For example, infants of mothers in the emotionally and physically abused group with intrafamilial violence exposure showed significantly low birth weight (Hemady et al, 2022); the class of household poverty and child discrimination showed the highest unmet care coordination needs (Anyigbo et al, 2021); children in the class of parental mental illness and poverty demonstrated the highest chronic condition and special healthcare needs (Lanier et al, 2018); adolescents experiencing neighborhood violence had the most severe chronic school absenteeism (Stempel et al, 2017); women in the sexual abuse/household dysfunction ACEs class had the weakest partner social support network during pregnancy (Napier et al, 2023); and adults experiencing sexual abuse were most vulnerable to developing diabetes (Salas et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…F. Wang, Yuan, et al, 2022; Xiao et al, 2023; Yuan et al, 2022; Zhang et al, 2020), Cambodia (Miedema et al, 2023), Germany (Turner et al, 2021; Witt et al, 2019), Korea (Kim, Park, et al, 2022), Singapore (Liu et al, 2022), Spain (Aizpurua et al, 2023), Switzerland (Barra et al, 2018), Tanzania (Zietz et al, 2020), and the United Kingdom (Iob et al, 2021; Lacey, Bartley, et al, 2020; Lacey, Pinto Pereira, et al 2020; Lacey et al, 2022; MacLochlainn et al, 2022; Ross et al, 2022). Interestingly, one study sampled eight country sites across the Latin-American and Caribbean region, Europe, Africa, the Indian Subcontinent, and Asia (Hemady et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations